Welche Nationalparke braucht Deutschland? - Job, Hubert (Raumforschung und Raumordnung | Spatial Research and Planning, 2022)
National parks are the oldest and most popular category of protected areas worldwide. They focus on two main issues: firstly the protection of nature, undisturbed natural processes and the conservation of biodiversity. Due to the long history of cultural landscapes and the comparably dense population of Central Europe multifold conflicts in land use evolve. Therefore this target is difficult to achieve. Secondly nature tourism is a goal of national parks – last not least to make the idea of wilderness tangible. Being situated in structural weak regions of the rural periphery, national parks can be seen as instruments for regional development. Outdoor recreation and tourism offer this possibility, especially in sparsely settled regions with further declining population figures. Spatial planning institutions should care for this development, thus creating new regional identities in lagging areas in the long run. 20 national parks are claimed to be sufficient for Germany. They are to fill the blank gaps on a representative map of Central Europe’s biomes, including moorlands, riverine forests, beech- and mixed deciduous forests as well as marine environments. Especially large interconnected woodlands and former military training areas offer possibilities for future declarations of national parks. In order to fulfill the requirements of nature protection and visitor management national parks should cover an area of at least 10,000 ha.